The Female FTSE Board Report 2019: moving beyond the numbers - Vinnicombe, Susan; Atewologun, Doyin; Battista, Valentina (Cranfield University, 2019)
This year we see a more encouraging picture emerging in terms of the number of women on FTSE boards. Over the past 12 months the percentage of women on FTSE 100 boards has increased from 29% to 32%, so the 33% target set for 2020 is well in sight. In total 292 women hold 339 directorships on FTSE 100 boards. The percentage of female non-executive directors (NEDs) is at the all-time high of 38.9%, whilst the percentage of female executives remains worryingly low at 10.9%. There is also progress on the FTSE 250 boards with the percentage of women directors rising from 23.7% to 27.3% this year and the number of all male boards dropping to three, but still, three is too many. The percentage of female NEDs is now 32.8% but the percentage of female executivedirectors (EDs) remains low at 8.4%.